Mobile agent in data mining-based intrusion detection system - Mohd. Aizaini Maarof 194492; Masrul Amri Kamarudin 410261; Subariah Ibrahim; Malaysian Science and Technology Congress (2002 : Johor Bahru) 473396 (Skudai : Universiti Teknologi Malaysia, 2002)
03